Tvoje telo - moja bolečina - Krpič, Tomaž (Družboslovne razprave, 2010)
Nick Crossley's concept of marginal reflexive body techniques is used to develop the concept of auto-reflexive body techniques whose primary purpose is to work back upon the body of an acting individual so as to modify, maintain, or thematise the body of that actor in some way, yet still with the intention to induce certain emotions, feelings, thoughts and agencies in another individual. The author defines a body art performance as an artistic, social, cultural and political phenomenon where body art performers produce an event on/under the surface of their own body by employing different repulsive marginal auto-reflexive body techniques as an investment of (unpleasant) feelings and emotions in the bodies of spectators. A body art performance also serves as a vehicle for expressing private concerns about common issues in public.
Keywords: Sociologija kulture; Sociology of culture; Performance art; Performans (Umetnost); Človekovo telo; Human body; Pain; Bolečina; Čustva; Emotions; body art; človeško telo; gledalci